MEKANISME TATA KELOLA PERUSAHAAN DAN PENGUNGKAPAN RISIKO - Deivy Ridha Rifani; Christina Dwi Astuti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The aim of this study is to get empirical evidence of the effect of good corporate governance mechanism on risk disclosure. Independent variable in this study are proportion of board independent, size of audit committee, institutional ownership, frequency of board meeting, and quality of external auditor. Dependent variable are risk disclosure. The research data obtained from the annual report of company on the Indonesian Stock Exchange website. The sample in this study used 96 companies listed at Indonesia Stock Exchange (BEI) for 2013-2015, with 265 item. The sampling technique using purposive sampling method. The result of this study are size of audit committee, institutional ownership, and quality of external auditor have a positive significant effect on risk disclosure. Unfortunetly, proportion of board independent and frequency of board meeting has no effect on risk disclosure.